Shifts in Indonesian Translation of Red Queen Novel - Emmiyati, Nuri; Pandhika, Rama Kanyan (Journal of Islamic Culture and Literature (JICeL), 2020)
Shift may occur in translating the text from source language into target language, especially when the two languages have different characteristics both linguistically and culturally. This study aimed to describe the kinds of shift in the Indonesian translation of Red Queen novel, a novel written in English by Victoria Aveyard in which it was translated by Nuraini Mastura. A descriptive qualitative approach was used in collecting and analyzing the data. The data were specifically the uttrances of the main characters in the novel both in the original novel written in English and its Indonesian translation. The data were analyzed referring to Newmark’s theory of transposition or shift of translation. This study revealed that all kinds of transposition or shift occur in translation of Red Queen novel. They are automatic transposition, no grammar equivalence, different ways to express idea, and lexical gap replaced by grammar structure.